Optimalisasi Keterampilan Digital Guru SD Islam Terpadu melalui Pelatihan Pemanfaatan Aplikasi Canva untuk Media Pembelajaran Kreatif - Arin Wildani; Agus Budiyono; Ary Iswahyudi (Universitas Nurul Jadid, 2024)
The increasing demand for innovative and interactive learning media in education highlights the importance of enhancing teachers' digital competencies. This community service program, conducted under the Community Partnership Program (PKM), aimed to improve the digital skills of teachers at Integrated Islamic Elementary Schools in Pamekasan, particularly in utilizing Canva to create engaging and effective learning materials. The primary challenge identified was the low proficiency of teachers in using technology for developing creative and up-to-date media. To address this, a participatory approach was employed, combining theoretical instruction with hands-on practice. The training was implemented in stages, starting with basic hardware literacy and progressing to the application of Canva features for classroom-appropriate learning media. Strategies included providing training modules, live demonstrations, and group discussions to foster collaborative idea-sharing. The program's outcomes revealed a significant improvement in teachers' digital competence. Pre- and post-training assessments demonstrated an increase in hardware proficiency from 57.4% to 73.4%, alongside notable enhancements in Canva-related skills, such as creativity, usage frequency, and diversity of learning materials produced. Despite challenges posed by the limited digital literacy of senior teachers, the program successfully equipped participants with the skills to develop more engaging and diverse digital learning resources, ultimately fostering greater student participation and motivation..